Associations of vitamin D deficiency with postoperative gait and mortality among patients with fractures of the proximal femur - Gumieiro, David Nicoletti [UNESP]; Pereira, Gilberto José Cação [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Ricciardi, Carlos Eduardo Inácio [UNESP]; Damasceno, Erick Ribeiro [UNESP]; Funayama, Bruno Schiavoni [UNESP] (Thieme, 2015)
To assess whether serum vitamin D concentration is associated with gait status and mortality among patients with fractures of the proximal femur, six months after suffering the fracture. Consecutive patients aged ≥65 years with fractures of the proximal femur, who were admitted to the orthopedics and traumatology ward of our service between January and December 2011, were prospectively evaluated. Clinical, radiological, epidemiological and laboratory analyses were performed, including vitamin D. The patients underwent surgery and were followed up as outpatients, with return visits 15, 30, 60 and 180 days after discharge, at which the outcomes of gait and mortality were evaluated. Eighty-eight patients were evaluated. Two of them were excluded because they presented oncological fractures. Thus, 86 patients of mean age 80.2 ± 7.3 years were studied. In relation to serum vitamin D, the mean was 27.8 ± 14.5 ng/mL, and 33.7% of the patients presented deficiency of this vitamin. In relation to gait, univariate and multivariate logistic regression showed that vitamin D deficiency was not associated with gait recovery, even after adjustment for gender, age and type of fracture (OR: 1.463; 95% CI: 0.524-4.088; p = 0.469). Regarding mortality, Cox regression analysis showed that vitamin D deficiency was not related to its occurrence within six months, even in multivariate analysis (HR: 0.627; 95% CI: 0.180-2.191; p = 0.465). Serum vitamin D concentration was not related to gait status and/or mortality among patients with fractures of the proximal femur, six months after suffering the fracture.
Keywords: Femoral fractures; Gait; Mortality; Vitamin d